Fabrication of foamed glass by valorization of ferrochromium slags and flint container glass waste - Kurtuluş, Recep; Kavas, Taner (International Symposium on Innovations in Civil Engineering and Technology)
Ferrochromium processes generate a vast quantity of ferrochromium slags which are accumulated in landfills. Not only economical uselessness but also detrimental environmental effects occur due to the accumulation of these wastes in nature. In the present study, based upon great opportunity of utilization of different waste materials in foam glass systems, the ferrochromium slags, supplied from Antalya ETİ Elektrometalurji Inc., with varying amounts of 10, 20 and 30 in wt.% were added in flint container glass (soda-lime-silica) waste obtained from municipal waste storage. A mixture of water glass and glycerol was also used as foaming agent while sufficient content of water was included as moisturizer in batch mixture. The samples were heated to the temperature of 850 °C with the heating rate of 10 °C/min, and then were kept for 30 min at the peak temperature. The valorisation of ferrochromium slags in foam glass systems were successfully fabricated by evaluating the properties of bulk density, porosity, water absorption and compressive strength. The results have a promising aspects and serve as a basis for advances in waste derived products to foster circular economy model in the perspective of zero waste. Further, a lightweight foam glass having 0.365 g/cm3 of bulk density with satisfactory mechanical properties having 1.48 MPa of compressive strength can be used in building applications.
Keywords: Ferrochromium Slags; Flint Container Glass Waste; Foamed Glass; Lightweight Materials; Waste Valorisation